2017
DOI: 10.3390/en10010123
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thermal-Electric Cross Coupling on Heat Transport in Nanofluids

Abstract: Nanofluids have an enhanced thermal conductivity compared with their base fluid. Although many mechanisms have been proposed, few of them could give a satisfactory explanation of experimental data. In this study, a mechanism of heat transport enhancement is proposed based on the cross coupling of thermal and electric transports in nanofluids. Nanoparticles are viewed as large molecules which have thermal motion together with the molecules of the base fluid. As the nanoparticles have surface charges, the motion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 54 publications
(83 reference statements)
0
11
0
Order By: Relevance
“…According to the review article by Lomascolo et al [29], the thermal conductivity of a nanofluid may increase linearly with the nanoparticle volume concentration, but in some cases the increase is non-linear. Many experimental studies [61], theoretical analysis/modelling [11,61] and molecular dynamics simulations [62][63][64][65][66] have attempted to reveal the complex mechanism of the thermal conductivity of nanofluids and the heat transfer between the fluid and the nanoparticles. There have also been many studies measuring the thermal conductivity of nanofluids; proper correlations provided by these studies are useful for engineering simulations [27,67,68].…”
Section: The Heat Flux Vectormentioning
confidence: 99%
See 1 more Smart Citation
“…According to the review article by Lomascolo et al [29], the thermal conductivity of a nanofluid may increase linearly with the nanoparticle volume concentration, but in some cases the increase is non-linear. Many experimental studies [61], theoretical analysis/modelling [11,61] and molecular dynamics simulations [62][63][64][65][66] have attempted to reveal the complex mechanism of the thermal conductivity of nanofluids and the heat transfer between the fluid and the nanoparticles. There have also been many studies measuring the thermal conductivity of nanofluids; proper correlations provided by these studies are useful for engineering simulations [27,67,68].…”
Section: The Heat Flux Vectormentioning
confidence: 99%
“…One of the most interesting applications of such efforts is the addition of additives to liquids (base fluids) [6] to reduce drag or to enhance heat transfer. In recent years, nanofluids, which are suspensions composed of base fluids and different types of nanoparticles, have received much attention for their outstanding performance on enhancing heat transfer efficiency [6][7][8][9][10][11][12][13][14]. In addition, nanofluids have the advantage of high mobility, better suspension stability, smaller pressure drop and less mechanical abrasion, etc.…”
Section: Introductionmentioning
confidence: 99%
“…6.356 (6) where µ f is the viscosity of the base fluid. The corresponding kinematic viscosity of the nanofluid can be obtained by ν n f = µ n f /ρ n f .…”
Section: Stress Tensormentioning
confidence: 99%
“…According to the review articles [31,32], the thermal conductivity and viscosity usually increase non-linearly in the function of nanoparticle volume concentration. For revealing the mechanism of the thermal and momentum diffusivity of nanofluids and the thermal/dynamic performance at the interface between the fluid and nanoparticles, many works based on experiments [33], theoretical analysis/modelling [6,33] and molecular dynamics simulations [34][35][36][37] have been performed. For example, some works indicated that the viscosity of the nanofluids is dependent on the nanoparticles concentration due to the apparently enhanced-viscosity of the base fluid near the solid surface caused by the surface force effects at small scales [29,35,36].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation